Traditional Islamic Religious Practice Arguments: Criticism of The Concept of Bid'ah of Islam Salafi-Wahabi - Sofyan A. P. Kau; Zulkarnain Suleman; Irwan (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This paper discusses traditional Islamic criticism of the concept of heresy in Salafi Islam, categorizing every new act in religion as iconoclastic heresy. Based on this concept of heresy, ritual ceremonies and practices of traditional Islamic religious traditions are classified as acts of heresy. Through literature research based on literary document sources using abstractive inductive logic methods and content analysis, this study found that ritual ceremonies and practices of traditional Islamic religious traditions are not acts of heresy because they are based on theorem (al-Quran, hadith and allegiance) it is new. New actions (mutants) are categorized as bid'ah if they conflict with the Quran, hadith, and a tsar. Traditional Islam criticizes the concept of heresy in Salafi-Wahhabi Islam for being ahistorical because several traditions show that the innovation of a friend, tâbi'u tâbi'uttab'în, while this innovation was not ordered and practiced by the Prophet; instead, was carried out by the generation of the Salaf.